2021
DOI: 10.3389/fneur.2021.625042
|View full text |Cite
|
Sign up to set email alerts
|

Years of Life Lost Due to Premature Death and Their Trends in People With Selected Neurological Disorders in Shanghai, China, 1995–2018: A Population-Based Study

Abstract: Background: Neurological disorders are the leading cause of long-term disability and the second leading cause of death in the world. We aimed to characterize the long-term trends in mortality and disease burden of selected neurological disorders and quantitatively analyze the contributions of demographic and non-demographic factors on the mortality of selected neurological disorders in Shanghai, China, 1995–2018.Methods: Mortality data were derived from the Vital Statistics System of Pudong New Area, Shanghai,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Age-specific mortality rates were calculated for the following age groups: 0–4 years, 5–14 years, 15–29 years, 30–44 years, 45–59 years, 60–69 years, 70–79 years, and ≥80 years. YLL was used to investigate the burden of liver cancer according to method and formula proposed in previous studies ( 11 , 15 ). Temporal trends in the mortality, YLL, and YLL rate from 1973 to 2019 were examined using Joinpoint Regression Program (version 4.3.1.0, National Cancer Institute, MD, USA) and expressed as an average annual percentage change (AAPC) with corresponding 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-specific mortality rates were calculated for the following age groups: 0–4 years, 5–14 years, 15–29 years, 30–44 years, 45–59 years, 60–69 years, 70–79 years, and ≥80 years. YLL was used to investigate the burden of liver cancer according to method and formula proposed in previous studies ( 11 , 15 ). Temporal trends in the mortality, YLL, and YLL rate from 1973 to 2019 were examined using Joinpoint Regression Program (version 4.3.1.0, National Cancer Institute, MD, USA) and expressed as an average annual percentage change (AAPC) with corresponding 95% confidence interval (CI).…”
Section: Methodsmentioning
confidence: 99%
“…An age-period-cohort analysis showed that effect attributed to population aging was the most important demographic factor in the mortality of liver cancer compared with period and cohort effect, and the mortality risk increased gradually with age ( 10 ). Non-demographic factors such as economic level, access to healthcare services, improvement of medical technology, promotion of residents' health awareness, and changed living environment are caused by circumstances beyond the individual's control ( 11 ). However, the contribution of demographic and non-demographic factors on the mortality of liver cancer have not been quantitatively analyzed in China.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rates of each year from 2006 to 2020, compared with the 2005 data, caused by demographic and non-demographic factors were estimated by the decomposition method, in which mortality rates were calculated and compared for each 5-year age group, from 0 to 4 to ≥85 years ( 8 ). All statistical analyses were conducted using SPSS (version 21.0; SPSS, Inc., Chicago, IL, USA) and R (version 3.4.3).…”
Section: Methodsmentioning
confidence: 99%
“…To adjust the effect of population size on total YLL in different locations, we used the YLL rate as a health outcome. Crude rates of YLL were calculated per 100,000 people for each location using the annual population (Luo et al 2021 ; Majdan et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%